Crystalline protein profiling and cry gene detection in Bacillus thuringiensis strains isolated during epizootics in Cydia pomonella L. - Konecka, Edyta; Baranek, Jakub; Kaznowski, Adam (Biological Letters, 2015)
The composition of Bacillus thuringiensis crystalline inclusions was characterized in 18 strains: 12 isolates were obtained from the intestinal tract of Cydia pomonella larvae during epizootics, 2 isolates were cultured from Leucoma salicis larvae taken from their natural populations, and 4 reference strains. The number and molecular mass of B. thuringiensis crystalline proteins (Cry and Cyt) was estimated by the sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). The crystals contained 1-8 proteins with molecular masses of 36-155 kDa. The toxin profiles differed both quantatively and qualitatively. The B. thuringiensis MPU B9 isolate had the highest number and diversity of Cry toxins. The analysis of crystal composition by SDS-PAGE was insufficient to detect groups and subgroups of Cry proteins. We identified 20 groups and 3 subgroups of Cry and Cyt crystalline toxins. Only one epizootic strain harboured cry25. In single reference strains, the cry1H, cry10 and cry25 genes were found. We did not find any correlation between the occurrence of cry genes and electrophoretic protein profiles of crystalline toxins.